Kesepian dengan Psychological Well Being pada Wanita Lajang Dewasa Awal : Ajeng Yistiani, Yulia Fitriani - Yistiani, Ajeng; Fitriani, Yulia (SOCIAL PHILANTHROPIC, 2024)
An early adult individual has a task in completing the process of development, one of which is choosing a life partner, Cultural changes that are currently growing regarding single young adult women. The negative influence of singleness is loneliness, less friendly relationships that can cause low psychological well-being of a person. The purpose of this study was to determine the relationship between loneliness and psychological well-being in early adult single women in city x. This study used a quantitative approach with Spearman's non-parametric correlation method. The sampling technique used was nonprobability sampling purposive sampling with subjects as many as 115 respondents. The results showed that there was a correlation between the variable loneliness and the variable psychological well being, so it can be stated that there is a negative relationship between loneliness and psychological well being in early adult single women in city x. This means that loneliness plays a significant role in the psychological well-being of an early adult single woman